The Impact of The Digital Accounting System on Financial Reporting Accuracy - Mathan, Dr.N.; Selvarajan , Sujai; Singh , Dukhbhanjan; Khurana , Shivam; Mishra , Smita; Mohammed , Dr.Shoaib; Mishra , Dr.BibhutiBhusan (International Journal of Accounting and Economics Studies, 2025)
Most organizations in a variety of sectors have embraced digital transformation for the purpose of improving their operations and productivity in the rapidly changing digital landscape of today. In emerging economies, the environment of financial reporting and accountability is transforming because of digital transformation, which encourages heightened efficiency and transparency. This growth is being fueled by the adoption of leading-edge technology such as blockchain, cloud computing, and AI, which is revolutionizing traditional financial processes. In emerging economies, where issues of unequal rules, inadequate infrastructure, and limited access to capital persist, digital transformation offers a means to enhance financial reporting and accountability structures. This capacity increases transparency, which fortifies decision-making procedures and boosts stakeholder trust. Digital transformation of the accounting profession has had profound implications for financial reporting and analysis methods. This study investigates the ways in which digital transformation affects technology adoption.